Indução de hipotermia terapêutica em recém-nascidos com diagnóstico de encefalopatia hipóxico-isquêmica - Binkowski, Raquel Trautenmüller Kerber (2013)
This study aimed to develop and implement a therapeutic hypothermia protocol in newborns with Hipoxic Ischemic Encephalopathy and compare the short term outcomes with a historical control group. Therefore, this study was divided in two parts: the first one consisted in a literature review in order to develop an hypothermia protocol. In the second part this protocol was applied in all neonates with moderate or severe Hypoxic Ischemic Encephalopathy admitted to the Neonatal Intensive Care Unit of Santa Maria University Hospital. The hypothermia protocol, which consisted in reducing axillary temperature of the newborn to 33.2ºC for a period of 72 hours, was applied in 6 neonates with Hypoxic Ischemic Encephalopathy admitted to the Neonatal Intensive Care Unit between September 2012 to March 2013. Outcomes during the hospital course and status at discharge (mortality, length of stay and disabilities) were compared with a historical control group. For this, data from 18 newborns with Hipoxic Ischemic Encephalopathy admitted at the same unit from 2003 to 2011 were collected from medical records. Disabilities were defined as any of the following: use of antiepileptic drugs, use of feeding tube, abnormalities in the neurological examination. Hypothermia group had a higher incidence of hypotension (p = 0.001), coagulopathy (p = 0.000) and bleeding (p = 0.001) during the procedure but they did not result in major adverse events. The mortality rate was significantly lower in hypothermia group (p = 0.02) as well as the presence of disabilities at hospital discharge (p = 0.04). We concluded that therapeutic hypothermia for treatment of Hypoxic Ischemic Encephalopathy in newborn infants seems to be a safe and effective procedure having a significant impact on the mortality rate and improving the neurodevelopmental in short term.